SOCIOLINGUISTIC COMPETENCE AND BARRIERS TO ITS IMPLEMENTATION: A CASE STUDY OF SECONDARY EFL TEACHERS IN QATAR - Telal Mirghani Khalid; Ali Ahmed Suleiman (English Education Department at FKIP Nommensen University, 2026)
Communicative competence, particularly its sociolinguistic component, is essential for effective English language teaching. However, EFL teachers face significant challenges in integrating sociolinguistic competence into classroom practice. This study examined Qatari secondary school EFL teachers’ knowledge of communicative competence, their beliefs regarding the teaching of sociolinguistic competence, perceived learning needs, and major hindrances to implementation. A quantitative survey conducted with 70 EFL teachers from two secondary schools in Doha, Qatar, using purposive sampling. Data was collected through a structured 5-point Likert-scale questionnaire covering four dimensions: teachers’ communicative competence knowledge, beliefs about teaching sociolinguistic competence, 21st-century learning needs, and perceived barriers. The instrument showed acceptable reliability (Cronbach’s α = 0.76). Results indicated strong self-reported knowledge of communicative competence (M = 4.39) and regular application in lesson planning (M = 4.20). Teachers strongly supported integrating target-culture knowledge but expressed scepticism about students’ sociolinguistic awareness. The primary barriers limited to authentic exposure to English (M = 4.41), insufficient time for material development (M = 4.29), and students’ difficulty understanding cultural norms. The findings highlight a significant gap between theoretical knowledge and practical implementation, emphasising the necessity of targeted professional development and curriculum reform in EFL contexts.